Utilization Of Digital Library To Increase Reading Interest In Elementary School Students - Yuli Mulyawati, Arita Marini (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
The existence of a school library information system can improve the quality and speed of the service process for library users so that it can facilitate the teaching and learning process in the school environment. The purpose of this research is to find out the use of digital libraries can increase the reading interest of elementary school students. The method used in this research is Literature review. Literature review is a scientific study that focuses on one particular topic. The literature review will provide an overview of the development of a particular topic. Literature review will allow a researcher to identify a theory or method, develop a theory or method, identify gaps that occur between a theory and its relevance in the field / to a research result. The results of the study stated that with a digital library, students no longer need to bother bringing books to read or study, only by opening the digital library application, students can access all sources of information in the digital library. In the digital library, many things can be found, be it e-books, pictures, magazines, story books and so on that are already stored in the digital library. The conclusion is that the current use of digital libraries is very much needed in an effort to be effective in reading literacy so that it can increase student interest in reading. However, the weakness is that currently there are not many schools that have not utilized the applications used in making digital libraries so that access is still very little